SOME INITIAL DISCUSSIONS ON PHENOMENON OF INTERNAL WAVE IN COASTAL WATERS OF CENTRAL VIETNAM - Son, Tong Phuoc Hoang; Chung, Tran Van; Huan, Nguyen Huu; Tien, Ngo Manh (Vietnam Journal of Marine Science and Technology, 2016)
Internal waves often occur in the East Vietnam Sea and have been determined mainly based on RADAR images. By means of dataset of VNREDSAT-1 satellite images and other imagery sources, for the first time, internal waves in the East Vietnam Sea have been identified by multispectral images; Also the formation mechanism of internal wave in the nearshore waters of Central Vietnam has been found. The analytical results show that the phenomenon of internal wave occurs in the nearshore waters of Central Vietnam mainly in the Southwest monsoon season (from June to September every year) and is located along the edge of the continental shelf. Internal waves formed along the waters of Central Vietnam mainly include the signals that have been generated at the shelf by large waves, through the basin from Luzon Strait. The study results have discovered a new applied aspect of VNREDSAT-1 satellite images in oceanographic research in general and detailed studies on internal waves in particular.